2018
DOI: 10.1093/mnras/sty2958
|View full text |Cite
|
Sign up to set email alerts
|

The New Numerical Galaxy Catalogue (ν2GC): properties of active galactic nuclei and their host galaxies

Abstract: We present the latest results of a semi-analytic galaxy formation model, "New Numerical Galaxy Catalogue", which utilises large cosmological N-body simulations. This model can reproduce many statistical properties of galaxies at z 6. We focus on the properties of active galactic nuclei (AGNs) and supermassive black holes, especially on the accretion timescale onto black holes. We find that the number density of AGNs at z < 1.5 and at hard X-ray luminosity < 10 44 erg/s is underestimated compared with recent ob… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
67
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(71 citation statements)
references
References 180 publications
4
67
0
Order By: Relevance
“…Menci et al (2014) find that in their semi-analytic model disc instabilities can provide enough black hole accretion to reproduce the observed AGN luminosity functions up to z ≈ 4.5, but are not likely to be dominant for the highest luminosity AGN or at the highest redshifts. In contrast, Shirakata et al (2018) find that the primary trigger of AGN at z ≤ 4 in their semi-analytic model is mergers, whilst disc instabilities are essential for fuelling moderate luminosity AGN at higher redshifts. The hydrodynamical simulation Horizon-AGN found that only ∼ 35 per cent of black hole mass in local massive galaxies is directly attributable to merging, with the majority of black hole growth instead growing via secular processes (Martin et al 2018).…”
Section: Black Hole Growth Mechanismsmentioning
confidence: 88%
“…Menci et al (2014) find that in their semi-analytic model disc instabilities can provide enough black hole accretion to reproduce the observed AGN luminosity functions up to z ≈ 4.5, but are not likely to be dominant for the highest luminosity AGN or at the highest redshifts. In contrast, Shirakata et al (2018) find that the primary trigger of AGN at z ≤ 4 in their semi-analytic model is mergers, whilst disc instabilities are essential for fuelling moderate luminosity AGN at higher redshifts. The hydrodynamical simulation Horizon-AGN found that only ∼ 35 per cent of black hole mass in local massive galaxies is directly attributable to merging, with the majority of black hole growth instead growing via secular processes (Martin et al 2018).…”
Section: Black Hole Growth Mechanismsmentioning
confidence: 88%
“…where tstart and tacc are the starting time of the accretion and the accretion timescale per one accretion event, respectively. We use the same model of the accretion timescale as Shirakata et al (2019), tacc = α bulge t dyn,bulge +t loss . The first term of the right-hand side is proportional to the dynamical time of their host bulges, t dyn,bulge , where the values of free parameter, α bulge , is 0.58.…”
Section: Smbh Growth Modelmentioning
confidence: 99%
“…circumnuclear discs) and accretion disc. We define t loss as t loss,0 (MBH/M ) γ BH (∆Macc/M ) γgas , where the free parameters, t loss,0 , γBH, and γgas, are 1.0 Gyr, 3.5, and -4.0, respectively (see Shirakata et al 2019). The AGN bolometric luminosity is described withṁ ≡ MBH/Ṁ Edd (Ṁ Edd = L Edd /c 2 ) as…”
Section: Smbh Growth Modelmentioning
confidence: 99%
See 2 more Smart Citations